IMPROVING STUDENTS’ UNDERSTANDING OF ENGLISH SENTENCES THROUGH UNDERSTANDING OF SENTENCE PATTERNS - Mainar Fitri (Indonesian Journal of Integrated English Language Teaching, 2017)
Based on the researcher’s observation in teaching and learning process, there were some problems faced by the students in understanding of English sentences of different types of texts (genre). The problems consisted of: (1) The students did not know the key ideas and details of English sentences. (2) the students were not able to differentiate between key ideas and less important ideas in sentences. To solve those problems, it was important to do a class action research by using a strategy of understanding sentence patterns. There were 2 aims of this research. The first aim was to explain to what extent students’ understanding of sentence patterns can better improve students’ understanding of English sentences. Secondly, to explain what factors influence the changes of students’ understanding of English sentences. This research consisted of three cycles. The result of the research showed that the strategy of understanding of sentence patterns could improve students’ understanding of English sentences. The improvement could be seen from the students’ average scores in the tests of understanding of English sentences which improved before the cycle into cycles. The average scores consisted of 28.7, 32.4, 56.4 and 60.6. the students’ average score improved 3.7 in cycle 1, 1.24 in cycle 2 and 4.2 in cycle 3. So, the improvement of understanding of English sentences before cycle into cycles was 31.9.   So, it can be concluded that the strategy of teaching sentence patterns improves students’ understanding of English sentences. It is caused by some factors. The factors are the teacher’s treatment, classroom atmosphere and students’ motivation in learning process.